A model for the electromagnetic spectrum of the inner jets of Centaurus A - Orellana, Mariana Dominga (2009)
Centaurus A, the closest active galaxy, has been detected from radio to high-energy gamma-rays. The synchrotron radiation by extremely high energy protons may be a suitable mechanism to explain the MeV to GeV emission detected by the instruments of the Compton Gamma-Ray Observatory, as coming from the inner jets. This scenario requires a relatively large magnetic field of about 10^4 G that could be present only close to the central black hole. We investigate the spectral energy distribution (SED) resulting from a one-zone compact acceleration region, where both leptonic and hadronic relativistic populations arise. We present here results of such a model, where we have considered synchrotron radiation by primary electrons and protons, inverse Compton interactions, and gamma-ray emission originated by the inelastic hadronic interactions between relativistic protons and cold nuclei within the jets themselves. Photo-meson production by relativistic hadrons were also taken into account, as well as the effects of secondary particles injected by all interactions. The internal and external absorption of gamma rays is shown to be of great relevance to shape the observable SED, which was also recently constrained by the results of HESS.